Phylogenomics reveals that asaia symbionts from insects underwent convergent genome reduction, preserving an insecticide-degrading gene - Comandatore, Francesco; Damiani, Claudia; Cappelli, Alessia; Ribolla, Paulo Eduardo Martins [UNESP]; Gasperi, Giuliano; Gradoni, Francesco; Capelli, Gioia; Piazza, Aurora; Montarsi, Fabrizio; Mancini, Maria Vittoria; Rossi, Paolo; Ricci, Irene; et al. (American Society for Microbiology, 2021)
The mosquito microbiota is composed of several lineages of microorganisms whose ecological roles and evolutionary histories have yet to be investigated in depth. Among these microorganisms, Asaia bacteria play a prominent role, given their abundance in the gut, reproductive organs, and salivary glands of different mosquito species, while their presence has also been reported in several other insects. Notably, Asaia has great potential as a tool for the control of mosquito-borne diseases. Here, we present a wide phylogenomic analysis of Asaia strains isolated from different species of mosquito vectors and from different populations of the Mediterranean fruit fly (medfly), Ceratitis capitata, an insect pest of worldwide economic importance. We show that phylogenetically distant lineages of Asaia expe-rienced independent genome reductions, despite following a common pattern, characterized by the early loss of genes involved in genome stability. This result high-lights the role of specific metabolic pathways in the symbiotic relationship between Asaia and the insect host. Finally, we discovered that all but one of the Asaia strains included in the study possess the pyrethroid hydrolase gene. Phylogenetic analysis revealed that this gene is ancestral in Asaia, strongly suggesting that it played a role in the establishment of the symbiotic association between these bacteria and the mosquito hosts. We propose that this gene from the symbiont contributed to initial pyrethroid resistance in insects harboring Asaia, also considering the widespread production of pyrethrins by several plants. IMPORTANCE We have studied genome reduction within several strains of the insect symbiont Asaia isolated from different species/strains of mosquito and medfly. Phylogenetically distant strains of Asaia, despite following a common pattern involving the loss of genes related to genome stability, have undergone independent genome reductions, highlighting the peculiar role of specific metabolic pathways in the symbiotic relationship between Asaia and its host. We also show that the pyreth-roid hydrolase gene is present in all the Asaia strains isolated except for the South American malaria vector Anopheles darlingi, for which resistance to pyrethroids has never been reported, suggesting a possible involvement of Asaia in determining resistance to insecticides.
Keywords: Asaia; Genome reduction; Pyrethroid hydrolase